Peluang Pariwisata Indonesia: Permasalahan Budaya Religius dengan Tuntutan Wisatawan di Pulau Bawean Jawa Timur - Bulqiyah, Hasanul; Fahrian, Denny (Universitas Medan Area, 2024)
The tourism industry is currently very prospective in improving the economy; in general, tourism must have value as an attraction for tourists. Bawean Island has various potentials for tourism development and is expected to become a regional icon in East Java Province. However, it is hampered by the religious culture embraced by the local community. It is feared that the increasing number of tourists will change society's culture, attitudes, and manners. This study aims to determine the obstacles to increasing tourism potential on Bawean Island, which are feared to change the existing culture. Qualitative research is used to explore tourism problems with the religious culture of local communities through the Gresik Regency Government, namely the Tourism Office and community leaders as subjects in this study; data collection is carried out using observation, documentation, and interview techniques. Research results show that the potential of tourism in Bawean Island is challenging to develop into a tourist island. Regional government policy regulations of Gresik Regency and East Java Province, such as regional regulations and regional spatial plans, have not been able to maximize tourism potential on Bawean Island. The strong religious culture of the local community is still a significant obstacle to developing tourism potential. There is a need to integrate cultural values ​​and sustainable tourism approaches. So far, the focus on this research concept has never been carried out by other researchers who have linked tourism development amidst the issue of high religiosity. What is new about this research is that not all cultures have values ​​that can be compared to opportunities for economic growth.